A Case of Extracorporeal Membrane Oxygenation as a Salvage Therapy for COVID-19-Associated Severe Acute Respiratory Distress Syndrome: Mounting Evidence - Kartikeya Rajdev MBBS; Lyndie A. Farr DNP; Muhammad Ahsan Saeed MD; Rorak Hooten MD; Joseph Baus MD; Brian Boer MD, PhD (SAGE Publishing, 2020)
Coronavirus disease 2019 (COVID-19) caused by a novel human coronavirus has led to a tsunami of viral illness across the globe, originating from Wuhan, China. Although the value and effectiveness of extracorporeal membrane oxygenation (ECMO) in severe respiratory illness from COVID-19 remains unclear at this time, there is emerging evidence suggesting that it could be utilized as an ultimate treatment in appropriately selected patients not responding to conventional care. We present a case of a 32-year-old COVID-19 positive male with a history of diabetes mellitus who was intubated for severe acute respiratory distress syndrome (ARDS). The patient's hypoxemia failed to improve despite positive pressure ventilation, prone positioning, and use of neuromuscular blockade for ventilator asynchrony. He was evaluated by a multidisciplinary team for considering ECMO for refractory ARDS. He was initiated on venovenous ECMO via dual-site cannulation performed at the bedside. Although his ECMO course was complicated by bleeding, he showed a remarkable improvement in his lung function. ECMO was successfully decannulated after 17 days of initiation. The patient was discharged home after 47 days of hospitalization without any supplemental oxygen and was able to undergo active physical rehabilitation. A multidisciplinary approach is imperative in the initiation and management of ECMO in COVID-19 patients with severe ARDS. While ECMO is labor-intensive, using it in the right phenotype and in specialized centers may lead to positive results. Patients who are young, with fewer comorbidities and single organ dysfunction portray a better prognosis for patients in which ECMO is utilized.